2022
DOI: 10.5863/1551-6776-27.2.172
|View full text |Cite
|
Sign up to set email alerts
|

An Audit on Pharmacists' Knowledge and Experience in Pediatric Care

Abstract: OBJECTIVE The aim of this study was to determine pharmacists' perceived knowledge and expertise required to deliver pharmaceutical care services to pediatric patients. METHODS Once ethical approval was obtained, a questionnaire was posted on local pharmacy groups. The questionnaire is composed of 4 domains: 1) Demographics, 2) Perceived knowledge of pediatric treatment and dosing, 3) Real-life pediatric cases, and 4) Future a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Unexpectedly, less than half of the respondents could accurately calculate the needed drug dose for a pediatric patient, Alqudah and colleagues had previously suggested that there is need for pharmacists to be adept at dosage calculations [7], which is a very important in preventing wrong dosing in this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, less than half of the respondents could accurately calculate the needed drug dose for a pediatric patient, Alqudah and colleagues had previously suggested that there is need for pharmacists to be adept at dosage calculations [7], which is a very important in preventing wrong dosing in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some drugs are unlicensed while some are used off-label in this population due to the non-inclusion of children in clinical trials until recently [4]. Previous studies established the need to include more pediatric courses in the undergraduate pharmacy curriculum [5][6][7], especially because the majority of pharmacists in Nigerian hospitals do not require more than the undergraduate pharmacy degree to practice. The knowledge and skill set needed to execute the basic pediatric pharmacy practice are essential in view of the number of pediatric patients encountered by hospital pharmacists in their practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation